Entheseal involvement in patients with systemic lupus erythematosus: an ultrasound study - Di Matteo, Andrea; Filippucci, Emilio; Cipolletta, Edoardo; Satulu, Iulia; Hurnakova, Jana; Lato, Valentina; De Angelis, Rossella; Horvath, Rudolf; Pavelka, Karel; Salaffi, Fausto; Grassi, Walter (Rheumatology (Oxford, England), 2018)
OBJECTIVES: The main objective of this study is to explore the prevalence and distribution of entheseal US changes in a cohort of SLE patients, taking as controls a group including both PsA patients and healthy subjects. The secondary objective is to investigate the correlation between the US findings and the clinical and serological data in SLE patients. METHODS: Clinical and US assessment of quadriceps, patellar and Achilles tendons, and plantar fascia entheses were performed by independent rheumatologists on 65 patients with SLE, 50 patients with PsA and 50 healthy subjects. US findings were identified according to the OMERACT definitions. In SLE patients, the correlation between the US changes and the clinical and laboratory findings was evaluated. RESULTS: US revealed one or more abnormalities in at least one enthesis in 44 out of 65 SLE patients (67.7%), 47 out of 50 PsA patients (94.0%) and 22 out of 50 healthy subjects (44.0%). In SLE patients, US findings indicating active inflammation were significantly more frequently detected than in healthy subjects (P < 0.001). The distal enthesis of the patellar tendon was the most commonly involved. The presence of power Doppler signal at the enthesis was an independent predictor of SLE disease activity (SLEDAI-2k P < 0.001, β = 0.52; musculoskeletal-BILAG P < 0.001, β = 0.56). CONCLUSION: The burden of entheseal sonographic changes was significantly higher in SLE patients than in healthy subjects, especially as regards active inflammation. The presence of power Doppler signal at the enthesis may represent a potential biomarker of SLE disease activity.
Keywords: dospělí; systémový lupus erythematodes; Female; Adult; ženské pohlaví; ultrasonografie dopplerovská; Foot; psoriatická artritida; lidé; Quadriceps Muscle; studie případů a kontrol; Achillova šlacha; stupeň závažnosti nemoci; Lupus Erythematosus, Systemic; noha (od hlezna dolů); Male; Case-Control Studies; ligamentum patellae; Arthritis, Psoriatic; Patellar Ligament; entezopatie; Achilles Tendon; lidé středního věku; mužské pohlaví; čtyřhlavý sval stehenní; Severity of Illness Index; Enthesopathy; Ultrasonography, Doppler; Middle Aged; Humans